In Situ Customized Illusion Enabled by Global Metasurface Reconstruction. (2nd February 2022) - Jia, Yuetian; Qian, Chao; Fan, Zhixiang; Ding, Yinzhang; Wang, Zhedong; Wang, Dengpan; Li, Er‐Ping; Zheng, Bin; Cai, Tong; Chen, Hongsheng
Abstract: Optical illusion has always attracted extensive attention, as it provides a superior self‐protection ability for both natural animals and human beings. A decade ago, this motivated the study and application of transformation optics, which provides a universal tool to manipulate light for invisibility cloaking and optical illusion. However, mainstream transformation‐optics‐based optical illusions are inherently hindered by the extreme requirements of metamaterial compositions in practice and unfavorably limited by the very large computational cost caused by their bulky state. To overcome these grand challenges, a novel and intelligent optical illusion supported by form‐free metasurfaces via a deep learning architecture is reported, which can not only render a similar illusion effect but also greatly reduces the parameter space in physics. Illustrative examples of conformal metasurfaces are presented, with a high‐fidelity inverse design from either the near‐ or far‐field in the simulation and experiment. Furthermore, a full set of intelligent systems is developed to benchmark the real‐world optical illusion applicability. The work brings the available illusion strategies closer to a wide range of in situ practical‐oriented applications and lays a foundation for the next generation of intelligent metamaterials. Abstract : An in situ intelligent optical illusion is demonstrated via a global metasurface reconstruction strategy. The intelligent optical illusion not only creates a customer‐defined illusion effect, but also greatly simplifies the mainstream but hard‐to‐reach transformation optics‐based methodology. Illustrative examples of conformal metasurfaces with high‐fidelity inverse design are presented, and a full set of intelligent systems is built to benchmark the real‐world illusion applicability.